The creative teaching & learning resource book - Best, Brin. 4 0 16; 1968- Thomas, Will; 5 ([London] ;;New York : Continuum International Pub. Group, 2008)
A resource book for professionals, focusing on climate for learning, teach and learning strategies, sustaining creative practice, and other topics.
Includes bibliographical references (p. 233-236) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Professional relationships. -- Creative teaching.;Effective teaching.;Teachers;Teaching.;Teachers.; 20; 2